Primary Malignant Melanoma of the Uterine Cervix: Rare Case Report - Lima, Carlos Anselmo (2023)
Introduction: Primary cervical melanoma is a rare and often challenging diagnosis, particularly in the presence of amelanotic lesions, where confirmation should be made through immunohistochemical methods. Despite aggressive treatment, the prognosis for this disease is typically poor. Case Report: A 79-year-old woman with a history of vaginal bleeding from a malignant cervical lesion. Initially, colposcopy examination revealed an ulcerated lesion of the exocervix, and biopsy confirmed a malignant neoplasm. However, following a radical abdominal hysterectomy, histopathological examination displayed a malignant epithelioid neoplasm, confirmed a malignant melanoma of the cervix through immunohistochemical assays. The patient received adjuvant chemotherapy and radiation therapy, but eventually experienced recurrence and died. Conclusion: The present report assesses a patient with an uncommon diagnosis of cervical melanoma, which, despite aggressive treatment, had an unfavorable outcome. However, thorough skin surveillance should be performed to correctly diagnose it as primary.